Pengembangan Aplikasi Bimbingan Haji Versi 2.0 Untuk Jamaah Pondok Pesantren Daarut Tauhiid (DT) - Satria Mandala; Vera Suryani; Erwid M Jadied (CV. Multi Kreasi Media, 2026)
The Daarut Tauhiid Islamic Boarding School (DT) has a ongoing commitment to nurturing the community, including improving the quality of Hajj and Umrah pilgrimages for its congregation. Although Hajj rituals have been carried out routinely, in practice DT pilgrims still face various challenges, such as the complexity of Hajj and Umrah procedures, limited access to contextual and direct guidance, and communication barriers between pilgrims and guides while in the Holy Land. These conditions have the potential to reduce the comfort, tranquility, and solemnity of the pilgrims in worship. As a follow-up to previous research and community service, this study proposes the further development of a mobile application for Hajj and Umrah guidance specifically for DT pilgrims. This application retains the core features that were developed previously, such as a means of communication between pilgrims and their guides, a comprehensive collection of prayers and guidelines for performing Hajj and Umrah, as well as motivational content and reminders for worship. This year, the application was further developed with the addition of strategic features to address issues still faced by pilgrims in the field. The main additional feature proposed is a location-based SOS feature that allows pilgrims to quickly and accurately share their location with Hajj guides or officials when experiencing an emergency, such as getting lost or separated from the group. In addition, the application also features customizable prayers and worship materials based on Hajj and Umrah groups, allowing guides to tailor guidance content to the needs, schedules, and characteristics of pilgrims in each group. Through the development of this application, it is hoped that DT pilgrims will receive more personalized, responsive, and contextual guidance during their Hajj and Umrah pilgrimages. This application not only serves as a technical support tool but also as a medium for continuous spiritual development. As a result, the quality of worship, sense of security, and spiritual experience of the pilgrims can significantly improve, in line with the vision of Pondok Pesantren Daarut Tauhiid in fostering a generation that excels in remembrance, reflection, and effort. Translated with DeepL.com (free version).